El Salvador : Report on Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report, 2011)
This report provides an assessment of fiscal transparency practices in El Salvador. Many of the code standards are followed by the country. In addition, fiscal data dissemination and monthly updating will be improved with the recent incorporation of the Finance Ministry's Fiscal Transparency Portal. Reports on the observance of standards and codes (ROSC) are undertaken on a voluntary basis. Rules and responsibilities are provided by the government to maintain the stability. Relations between government and the public and private sectors are discussed.